2020
DOI: 10.21203/rs.3.rs-28938/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Formyl peptide receptor agonist Ac2-26 alleviates neuroinflammation in a mouse model of pneumococcal meningitis

Abstract: BackgroundBacterial meningitis is, despite progress in research and the development of new treatment strategies, still a cause of severe neurological disability. The brain is protected from penetrating pathogens by the blood-brain barrier and the innate immune system. The invading pathogens are recognized by pattern recognition receptors including the G-protein coupled formyl peptide receptors (FPRs), which are expressed by immune cells of the central nervous system. FPRs show a broad spectrum of ligands inclu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…To date, no studies have reported the involvement of these genes in the occurrence and development of CRSwNP. A recent study has confirmed that the formyl peptide receptor agonist Ac2-26 exerts an anti-inflammatory effect in a mouse model of bacterial meningitis through the formamide peptide receptor 2 (FPR2) (Rüger et al, 2020). FPR2 agonists could stimulate the resolution of inflammation by inhibiting neutrophil chemotaxis and stimulating macrophage phagocytosis, which may be the key to the treatment of chronic inflammatory diseases (Asahina et al, 2020).…”
Section: Discussionmentioning
confidence: 96%
“…To date, no studies have reported the involvement of these genes in the occurrence and development of CRSwNP. A recent study has confirmed that the formyl peptide receptor agonist Ac2-26 exerts an anti-inflammatory effect in a mouse model of bacterial meningitis through the formamide peptide receptor 2 (FPR2) (Rüger et al, 2020). FPR2 agonists could stimulate the resolution of inflammation by inhibiting neutrophil chemotaxis and stimulating macrophage phagocytosis, which may be the key to the treatment of chronic inflammatory diseases (Asahina et al, 2020).…”
Section: Discussionmentioning
confidence: 96%